Preparation method of anti-fouling and injectable porous magnetic hydrogel and detection method of nitrite in pre-prepared vegetable by using anti-fouling and injectable porous magnetic hydrogel
By preparing a stain-resistant, injectable porous magnetic hydrogel on a glass carbon electrode, the problem of poor sensitivity and accuracy of traditional electrodes in complex food matrix is solved, and high sensitivity and low cost nitrites are achieved Testing, suitable for rapid detection of pre-made dishes.
Patent Information
- Application Number
- CN202411367070.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2024-12-27
AI Technical Summary
Traditional glassy carbon electrodes in complex food matrix have poor sensitivity and accuracy due to high catalytic potential and soiling effect, and CuFe2O4-modified hydrogels have not been reported in electrochemical sensors.
Use carboxymethyl chitosan, CuFe2O4 and dopamine to prepare anti-fouling, injectable porous magnetic hydrogels, modify glass carbon electrodes, build electrochemical sensors to detect nitrites, and use electrostatic attraction and pore structure to improve detection sensitivity. .
It realizes nitrite detection with high sensitivity, accuracy and reproducibility in complex pre-made vegetable substrates, with a linear range of 0.02μmol/L-2.25mmol/L and a minimum detection limit of 3.6nmol/L, which is suitable for rapid detection. Moreover, the synthesis of electrode modification materials is simple and low-cost.
Smart Images

Figure CN119192651A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of food safety detection, and in particular to an anti-fouling, injectable porous magnetic hydrogel and a method for detecting nitrite in pre-prepared dishes thereof. Background Art
[0002] As a common food additive, nitrite is widely used in pre-prepared dishes because of its ability to prevent food spoilage and lipid oxidation. However, long-term excessive consumption of nitrite may cause serious health crises to humans (such as tissue hypoxia and even cancer), because nitrite can not only oxidize hemoglobin carrying oxygen in the blood into ferric hemagglutinin, but also couple with amides / amines to form carcinogenic nitrosamines. Considering the potential hazards of nitrite, the development of a fast and reliable nitrite quantitative analysis technology is crucial to protect public health.
[0003] A variety of technical strategies for nitrite detection have been implemented, including ion chromatography, capillary electrophoresis, fluorescence sensors, and electrochemical sensors. Among these detection technologies, electrochemical sensors are considered to be a promising technology for detecting nitrite due to their low cost and fast response speed. However, traditional glassy carbon electrodes are often affected by high catalytic potential and fouling effects in complex food matrices, resulting in poor sensitivity and accuracy. Therefore, effective strategies must be adopted to address these limitations.
[0004] Three-dimensional porous nanomaterials can not only promote the transfer of molecules and ions, but also provide more binding sites for targets due to their unique structure, which has attracted widespread attention in the field of electrochemical sensing. As one of them, hydrogel is an ideal candidate material for electrode surface modification due to its hydrophilic three-dimensional network structure. However, the catalytic performance of pure hydrogel is weak and it is difficult to separate from the solution. Copper ferrite (CuFe2O4) nanoparticles have higher conductivity, good structural stability, low cost, excellent catalytic and magnetic properties than single-element transition metal oxides, and have a wide range of applications in electronics, sensing and catalysis. However, the strong magnetism and intermolecular dipole forces make CuFe2O4 easy to agglomerate and have poor dispersibility. So far, there has been no report on the construction of electrochemical sensors for nitrite detection based on CuFe2O4-modified hydrogels. Summary of the invention
[0005] In view of the above-mentioned prior art, the object of the present invention is to provide an anti-fouling, injectable porous magnetic hydrogel and a method for detecting nitrite in pre-prepared dishes thereof.
[0006] To achieve the above object, the present invention adopts the following technical solution:
[0007] In a first aspect of the present invention, there is provided an anti-fouling, injectable porous magnetic hydrogel prepared by the following method:
[0008] (1) dispersing carboxymethyl chitosan and CuFe2O4 in deionized water, vigorously stirring at room temperature for 50-70 min, then adding dopamine, and continuing to stir for 1.5-2.5 h to obtain a mixture A;
[0009] (2) dissolving sodium alginate in deionized water, adding polyethyleneimine solution, and stirring at room temperature for 2.0-2.5 hours to obtain a mixture B;
[0010] (3) Mixing mixture B with mixture A, and continuing to stir at room temperature for 3.0-3.5 hours to prepare an anti-fouling, injectable porous magnetic hydrogel.
[0011] Preferably, in step (1), the weight ratio of carboxymethyl chitosan, CuFe2O4 and dopamine added is (70-90): (15-25): (4-6).
[0012] Preferably, in step (2), the ratio of the added amounts of sodium alginate, deionized water and polyethyleneimine solution is (140-160) mg:6 mL:1 mL; and the concentration of the polyethyleneimine solution is 250.0 mg / mL.
[0013] Preferably, in step (3), the volume ratio of mixture A to mixture B is 4:(6-8).
[0014] The second aspect of the present invention provides the use of the porous magnetic hydrogel in the following (1) or (2):
[0015] (1) Detection of nitrite;
[0016] (2) Preparation of electrochemical sensor for detecting nitrite.
[0017] A third aspect of the present invention provides an electrochemical sensor for detecting nitrite in pre-prepared dishes, wherein the electrochemical sensor uses the glassy carbon electrode modified with the porous magnetic hydrogel as a working electrode.
[0018] Preferably, the drop coating amount of the porous magnetic hydrogel on the glassy carbon electrode is 40 to 120 μL / cm 2 .
[0019] Furthermore, the electrochemical sensor also includes a reference electrode and an auxiliary electrode; the reference electrode is a saturated calomel electrode, and the auxiliary electrode is a platinum electrode.
[0020] A fourth aspect of the present invention provides a method for detecting nitrite in pre-prepared dishes, comprising the following steps:
[0021] (1) The working electrode, reference electrode and auxiliary electrode in the electrochemical sensor constitute a three-electrode system. The working electrode is immersed in a nitrite standard solution of different concentrations and incubated within the window potential using differential pulse voltammetry. The corresponding current value Ip is recorded. The Ip curve is plotted with the concentration of the nitrite standard solution as the horizontal axis and the current value Ip as the vertical axis. P -C working curve;
[0022] (2) Using the working curve drawn in step (1), the content of nitrite in the pre-treated prepared food sample to be tested is detected.
[0023] Preferably, in step (1), the window potential is 0.3-1.4 V; and the nitrite standard solutions of different concentrations are prepared from PBS solutions.
[0024] Preferably, in step (2), the pretreatment method of the pre-prepared dish to be tested is: adding a saturated borax solution and hot water to the pre-prepared dish to be tested, ultrasonically mixing and then boiling; cooling to room temperature, adding potassium ferrocyanide and zinc acetate solution to the extract, letting it stand and then filtering, evaporating the filtrate to dryness, and dissolving the residue with PBS.
[0025] The above-mentioned pretreatment method is used to extract nitrite, wherein borax can absorb NO2 decomposed from nitrite, ensuring that the total amount of nitrite will not be decomposed and reduced due to heating, thereby effectively extracting nitrite from pre-prepared dishes and precipitating protein.
[0026] Beneficial effects of the present invention:
[0027] (1) The porous magnetic hydrogel prepared by the present invention has excellent anti-fouling properties, injectability, adsorption properties and electrochemical catalytic properties; among them, the "anti-fouling" property enables the constructed electrochemical sensor to prevent the accumulation of fat and protein in the pre-prepared food on the electrode surface through its own cleaning ability when detecting sodium nitrite in a complex pre-prepared food matrix, thereby reducing the interference of the pre-prepared food medium, thereby improving the sensitivity and accuracy of the constructed electrochemical sensor. The "injectable" property can accurately quantify the amount of hydrogel dripped on the electrode surface, thereby improving the reproducibility of the constructed electrochemical sensor in detecting nitrite. The adsorption property can accelerate the enrichment of nitrite on the electrode surface and improve the sensitivity of detection.
[0028] (2) The present invention uses an electrode modified with an anti-fouling, injectable porous magnetic hydrogel as a working electrode to construct an electrochemical sensor capable of highly sensitive detection of nitrite. Among them, the use of CuFe2O4 coated with polydopamine as a cross-linking agent can not only improve the uniformity, adsorption and electrocatalytic energy of the prepared anti-fouling, injectable porous magnetic hydrogel, but also generate a large number of pore structures in the hydrogel, providing more binding sites for the analyte, thereby improving the sensitivity and reproducibility of the electrochemical sensor for nitrite detection. In addition, the positively charged polyethyleneimine can accelerate the transfer speed of nitrite to the electrode surface through electrostatic attraction, which helps to achieve rapid detection of nitrite.
[0029] (3) The linear range of nitrite detection by the electrochemical sensor of the present invention is 0.02 μmol / L-2.25 mmol / L, and the minimum detection limit is 3.6 nmol / L, which can meet various detection needs. Moreover, compared with the national food safety standard - determination of nitrite and nitrate in food (GB5009.33-2016), the analytical method of the present invention can directly detect the treated sample liquid, shortening the detection time of nitrite, and is suitable for rapid detection of nitrite.
[0030] (4) The synthesis method of the electrode modification material in the present invention is relatively simple and environmentally friendly. Therefore, the electrochemical sensor prepared by the present invention has low cost, high sensitivity, short analysis time, and simple experimental operation, and is suitable for rapid detection of nitrite in various pre-prepared dishes. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 : Schematic diagram of the synthesis principle of the anti-fouling, injectable porous magnetic hydrogel of the present invention.
[0032] Figure 2 : SEM image of the anti-fouling, injectable porous magnetic hydrogel prepared in Example 1 of the present invention.
[0033] Figure 3 :A is the DPV curve of the electrochemical sensor prepared in Example 2 of the present invention for detecting nitrite of different concentrations. B is the standard curve of the electrochemical sensor prepared in Example 2 of the present invention for detecting nitrite. Figure 3 It can be seen that the linear range of the sensor for nitrite detection is 0.02μmol / L-2.25mmol / L, and the minimum detection limit is 3.6nmol / L.
[0034] Figure 4:A is an experimental diagram of the anti-interference of the electrochemical sensor prepared in Example 2 of the present invention for detecting nitrite; ((a) no interference, (b) ascorbic acid, (c) glucose, (d) sodium citrate, (e) L-lysine, (f) glutamic acid, (g) SO4 2- , (h)Cl - , (i) NO3 - , (j) HCO3 2- , (k)Fe 3+ , (l)Cu 2+ , (m)Zn 2+ and (n)K + ); B is a repeatability experimental diagram of the electrochemical sensor prepared in Example 2 of the present invention for detecting nitrite; C is a reproducibility experimental diagram of the electrochemical sensor prepared in Example 2 of the present invention for detecting nitrite; D is a stability experimental diagram of the electrochemical sensor prepared in Example 2 of the present invention for detecting nitrite.
[0035] Figure 5 : Schematic diagram of the method for detecting nitrite by the sensor prepared in Example 2 of the present invention.
[0036] Figure 6 : Investigation results of antifouling properties of hydrogel.
[0037] Figure 7 : Investigation results of injectable properties of hydrogel.
[0038] Figure 8 : Investigation results of electrocatalytic performance of hydrogel. DETAILED DESCRIPTION
[0039] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.
[0040] Terminology Note:
[0041] The "room temperature" mentioned in the present invention refers to a temperature of 15-30°C.
[0042] As mentioned above, the current methods for nitrite detection mainly include ion chromatography, capillary electrophoresis, fluorescence sensors and electrochemical sensors. Among these methods, the detection limit of ion chromatography is 217.39nmol / L, the detection limit of capillary electrophoresis is 15000nmol / L, and the detection limit of fluorescence sensor is 70nmol / L. In order to further improve the sensitivity of the electrochemical sensing platform for nitrite determination, designing suitable electrode modification materials is a huge challenge.
[0043] Based on this, the purpose of the present invention is to provide an electrochemical sensor based on an anti-fouling, injectable porous magnetic hydrogel and a method for detecting nitrite in pre-prepared dishes. During the synthesis process of the anti-fouling, injectable porous magnetic hydrogel of the present invention, the polydopamine formed in the carboxymethyl chitosan solution can adhere to the surface of CuFe2O4. The use of the polydopamine-coated CuFe2O4 as a cross-linking agent to prepare the hydrogel is conducive to the uniform dispersion of CuFe2O4 in the hydrogel, and can also make the hydrogel produce a pore structure, thereby providing more binding sites for the analyte. The abundant hydroxyl groups in ammonium alginate can be connected to polydopamine through hydrogen bonds, thereby improving the anti-fouling ability of the synthesized hydrogel. The active amino groups in polyethyleneimine can be connected to polydopamine through Schiff base bonds and hydrogen bonds. In addition, the positively charged polyethyleneimine can also be cross-linked with carboxymethyl chitosan and sodium alginate through electrostatic attraction to form an anti-fouling, injectable porous magnetic hydrogel (MHG).
[0044] In order to achieve rapid and sensitive detection of nitrite, the present invention uses an electrode modified with an anti-fouling, injectable porous magnetic hydrogel as a working electrode (MHG / GCE) to construct an electrochemical sensor capable of highly sensitive and rapid detection of nitrite in pre-prepared dishes. The detection principle is: under the action of an external current, nitrite can undergo a redox reaction on the surface of the modified electrode, generating an electrical signal at a specific position (+0.7V to +0.8V), thereby achieving quantitative detection of nitrite. Among them, the electrostatic attraction between the synthesized anti-fouling, injectable porous magnetic hydrogel and nitrite can accelerate the rate at which nitrite reaches the electrode surface; the addition of CuFe2O4 can improve the electrocatalytic activity of the synthesized hydrogel to nitrite, and the porous structure formed by the hydrogel can provide more electroactive sites for nitrite, thereby achieving highly sensitive and rapid detection of nitrite.
[0045] In order to enable those skilled in the art to more clearly understand the technical solution of the present application, the technical solution of the present application will be described in detail below in conjunction with specific embodiments.
[0046] The test materials used in the examples and comparative examples of the present invention are all conventional test materials in the art and can be purchased through commercial channels. The experimental methods without detailed conditions are carried out according to conventional test methods or the operating instructions recommended by the supplier.
[0047] Example 1: Preparation of antifouling, injectable porous magnetic hydrogel
[0048] The synthesis principle of antifouling and injectable porous magnetic hydrogels Figure 1 As shown, the specific preparation process is as follows:
[0049] (1) 1.35 g FeCl 3·6H2O and 0.43g CuCl 2· 2H2O was added to 80.0mL ethylene glycol and ultrasonically treated for 30min to form a clear solution. Then 2.5g CH3COONa was added to the solution and magnetically stirred at 50℃ for 30min to obtain a precursor dispersion. The precursor dispersion was placed in a 100mL stainless steel autoclave and reacted at 200℃ for 12h. After the reaction, the precipitate was collected by centrifugal washing with double distilled water (DDW) and ethanol and vacuum dried at 60℃ for 24h to obtain CuFe2O4 nanoparticles.
[0050] (2) 80.0 mg of carboxymethyl chitosan and 20.0 mg of CuFe2O4 nanoparticles were dispersed in 4.0 mL of deionized water and vigorously stirred at room temperature for 60 min. Then, 5.0 mg of dopamine was added to the mixture and the stirring was continued for 2.0 h until dopamine was spontaneously oxidized to the adhesive polydopamine to obtain mixture A.
[0051] 150.0 mg of sodium alginate was dissolved in 6.0 mL of deionized water, 1.0 mL of polyethyleneimine solution (250.0 mg / mL) was added, and stirring was continued at room temperature for 2.0 h to obtain a mixture B.
[0052] After the mixture A and the mixture B were mixed, stirring was continued for 3.0 h at room temperature until a hydrogel was formed, thereby preparing an anti-fouling, injectable porous magnetic hydrogel (MHG).
[0053] The MHG prepared in this example was analyzed by scanning electron microscopy. Figure 2 , it can be seen from the figure that the MHG has a wrinkled morphology, and the wrinkled black part in the figure is the porous structure of the MHG, which proves that the present invention successfully synthesized the MHG with a porous structure.
[0054] Example 2: Construction of an electrochemical sensor
[0055] Take the MHG prepared in Example 1 and drop it on the surface of the bare glassy carbon electrode. The drop amount is 50 μL / cm 2 , and dried naturally at room temperature to obtain the modified MHG / GCE electrode.
[0056] A three-electrode system was constructed using MHG / GCE electrode as the working electrode, saturated calomel electrode as the reference electrode, and platinum electrode as the auxiliary electrode to obtain an electrochemical sensor.
[0057] Example 3: Detection of nitrite
[0058] (1) The working electrode, reference electrode and auxiliary electrode in the electrochemical sensor prepared in Example 2 constitute a three-electrode system. The working electrode is immersed in different concentrations of nitrite standard solutions (0.02, 1, 10, 50, 100, 200, 500, 750, 1000, 1500, 2000 and 2250 μmol / L) prepared in PBS with a pH of 7.0 and incubated using differential pulse voltammetry within a potential window of 0.3-1.4 V, and the corresponding current value Ip is recorded; the working curve is plotted with the concentration of the nitrite standard solution as the abscissa and the current value Ip as the ordinate. Figure 3 ):I μA =-0.096C μM -1.142(R 2 =0.9981).
[0059] (2) Transfer 2.0 g of ground ham sample to a 150 mL conical flask. Add 7.0 mL of saturated borax solution (50.0 g / L) and 72.0 mL of water (about 70 °C), mix under ultrasound, and boil for 20 min. After cooling to room temperature, transfer 50.0 mL of the extract to a 100 mL volumetric flask, and then add 2.5 mL of K4Fe(CN) 6· 3H2O solution (106 g / L) and 2.5 mL (CH3COO)2Zn solution (220 g / L) were added to the extract to precipitate protein. The resulting mixture was diluted to 100 mL with DDW and filtered to remove any solids after standing for 30 min. 5.0 mL of the filtrate was evaporated to dryness at 60 °C, and then 5.0 mL PBS (pH 7.0) was added to redissolve the residue. Finally, the developed sensor was used to analyze the nitrite content in ham sausage.
[0060] Example 4: Methodological verification of MHG / GCE sensor for detecting nitrite
[0061] 1. Anti-interference inspection:
[0062] In order to study the anti-interference performance of the MHG / GCE sensor, the working electrode was immersed in a solution containing a series of possible interfering agents, including 100-fold excess (compared to the concentration of sodium nitrite) of inorganic ions (SO4 2- , Cl - , NO3 - , HCO3 - , Fe 3+ , Cu 2+ , Zn 2+ and K +The DPV curves were measured in 200 μmol / L sodium nitrite solution with 10 times excess (compared to the concentration of sodium nitrite) of organic compounds (ascorbic acid, glucose, sodium citrate, L-lysine and glutamic acid). Figure 4 AIt can be seen that the anti-interference performance of the sensor is satisfactory.
[0063] 2. Repeatability test:
[0064] In order to evaluate the measurement repeatability of the MHG / GCE sensor, six measurements were performed in 200 μmol / L sodium nitrite solution using a single MHG / GCE electrode pair. Figure 4 B shows that the sensor has good repeatability.
[0065] 3. Reproducibility study:
[0066] In order to test the reproducibility of the MHG / GCE sensor construction, six modified electrodes were prepared under the same conditions and used to analyze the same 200 μmol / L nitrite solution. Figure 4 C shows that the reproducibility of the sensor is acceptable.
[0067] 4. Long-term stability investigation:
[0068] In order to evaluate the stability of the MHG / GCE sensor, it was stored at 4°C for 30 days, and its DPV curve was measured in 200 μmol / L sodium nitrite solution every 5 days to record the change of peak current with storage time. Figure 4 It can be seen from D that the sensor has good long-term stability.
[0069] Comparative Example 1:
[0070] 80.0 mg of carboxymethyl chitosan was dispersed in 4.0 mL of deionized water and stirred vigorously at room temperature for 60 min, then dopamine was added to the mixture and stirred for 2.0 h until dopamine was spontaneously oxidized to polydopamine, an adhesive, to obtain mixture A. 150.0 mg of sodium alginate was dissolved in 6.0 mL of deionized water, 1.0 mL of polyethyleneimine solution (250.0 mg / mL) was added, and stirring was continued at room temperature for 2.0 h to obtain mixture B. After mixing mixture A and mixture B, stirring was continued at room temperature for 3.0 h until a hydrogel was formed, which was recorded as HG.
[0071] Comparative Example 2:
[0072] 1.35 g FeCl 3· 6H2O and 0.43g CuCl 2·2H2O was added to 80.0mL ethylene glycol and ultrasonically treated for 30min to form a clear solution. Then 2.5g CH3COONa was added to the solution and magnetically stirred at 50℃ for 30min to obtain a precursor dispersion. The precursor dispersion was placed in a 100mL stainless steel autoclave and reacted at 200℃ for 12h. After the reaction, the precipitate was collected by centrifugal washing with DDW and ethanol and vacuum dried at 60℃ for 24h to obtain CuFe2O4 nanoparticles.
[0073] Comparative Example 3:
[0074] 80.0 mg of carboxymethyl chitosan was dispersed in 4.0 mL of deionized water and stirred vigorously at room temperature for 60 min, then dopamine was added to the mixture and stirred for 2.0 h until dopamine was spontaneously oxidized to polydopamine, an adhesive, to obtain mixture A. 150.0 mg of sodium alginate was dissolved in 6.0 mL of deionized water and stirred for 2.0 h at room temperature to obtain mixture B. After mixing mixture A and mixture B, stirring was continued at room temperature for 3.0 h until a hydrogel was formed, which was recorded as HGwithout PEI.
[0075] Test Example 1: Investigation of the antifouling properties of hydrogel
[0076] The water contact angles of the hydrogel MHG prepared in Example 1 and the hydrogel HG prepared in Comparative Example 1 were measured. Figure 6 As shown, HG: CA = 23.16 ± 0.53°, MHG: CA = 20.80 ± 0.22°.
[0077] The smaller the water contact angle, the better the anti-fouling performance. Therefore, the hydrogel MHG prepared by the present invention has certain anti-fouling performance. By utilizing its anti-fouling performance, when detecting nitrite in a complex pre-prepared food matrix, the fat and protein that have not been removed in the pre-prepared food can be prevented from aggregating on the electrode surface through its own cleaning ability, thereby reducing the interference of the pre-prepared food medium, thereby improving the sensitivity and accuracy of the constructed electrochemical sensor.
[0078] Test Example 2: Investigation of the injectable properties of hydrogel
[0079] In 0 to 100s -1 At a shear rate of , the apparent viscosity of the hydrogel MHG prepared in Example 1, the hydrogel HG prepared in Comparative Example 1, and the hydrogel HG without PEI prepared in Comparative Example 3 were measured.
[0080] The results are as follows Figure 7As shown, the results show that: with the increase of shear rate, the viscosity of all samples gradually decreases, among which the viscosity of MHG is lower than that of HG without PEI and HG. This shear thinning property and relatively low viscosity give the material excellent injectability, which is conducive to applying a specific amount of MHG to GCE for sensor construction.
[0081] Experimental Example 3: Investigation of the electrocatalytic performance of hydrogel
[0082] The materials prepared in Comparative Examples 1 to 3 were used to construct electrochemical sensors according to the method of Example 2, and their DPV curves in 200 μM nitrite were measured.
[0083] The results are as follows Figure 8 As shown, the results show that in the hydrogel prepared by the present invention, the electrostatic attraction between PEI and the target object and the improvement of the dispersion performance of copper ferrite (CuFe2O4) nanoparticles in the hydrogel significantly improve the electrocatalytic ability of the prepared electrochemical sensor.
[0084] Test Example 4: Investigation of the adsorption properties of hydrogels
[0085] Transfer 2.0 g of ground ham sample to a 150 mL conical flask. Add 7.0 mL of saturated borax solution (50.0 g / L) and 72.0 mL of water (about 70 ° C), mix under ultrasound, and boil for 20 min. After cooling to room temperature, transfer 50.0 mL of the extract to a 100 mL volumetric flask, and then add 2.5 mL of K4Fe(CN) 6· 3H2O solution (106 g / L) and 2.5 mL (CH3COO)2Zn solution (220 g / L) were added to the extract to precipitate protein. The resulting mixture was diluted to 100 mL with DDW and filtered to remove any solids after standing for 30 min. 5.0 mL of the filtrate was evaporated to dryness at 60°C, and then 5.0 mL of PBS (pH 7.0) was added to redissolve the residue. The extract was filtered with a 0.22 μm filter membrane, and the content of nitrite in the extract was detected by UV-spectrophotometry according to the national standard method (GB 5009.33-2016) to be 5.27 ± 4.23 mg / kg.
[0086] The extract was divided into three parts, and equal amounts of the materials prepared in Example 1, Comparative Example 1 and Comparative Example 2 were placed in each part and mixed for 4 minutes. The materials prepared in Example 1, Comparative Example 1 and Comparative Example 2 were taken out, and the nitrite content in the extract was measured again, which was 2.96±1.58mg / kg, 4.02±1.98mg / kg and 3.89±2.54mg / kg, respectively. -1 .
[0087] The results show that the hydrogel material prepared by the present invention has a good adsorption effect on nitrite, can accelerate the enrichment of nitrite on the electrode surface, and improve the sensitivity of detection.
[0088] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. An anti-fouling, injectable porous magnetic hydrogel, characterized in that: Prepared by the following method: (1) dispersing carboxymethyl chitosan and CuFe2O4 in deionized water, vigorously stirring at room temperature for 50-70 min, then adding dopamine, and continuing to stir for 1.5-2.5 h to obtain a mixture A; (2) dissolving sodium alginate in deionized water, adding polyethyleneimine solution, and stirring at room temperature for 2.0-2.5 hours to obtain a mixture B; (3) Mixing mixture B with mixture A, and continuing to stir at room temperature for 3.0-3.5 hours to prepare an anti-fouling, injectable porous magnetic hydrogel.
2. The porous magnetic hydrogel according to claim 1, characterized in that: In step (1), the weight ratio of carboxymethyl chitosan, CuFe2O4 and dopamine added is (70-90): (15-25): (4-6).
3. The porous magnetic hydrogel according to claim 1, characterized in that: In step (2), the ratio of the added amounts of sodium alginate, deionized water and polyethyleneimine solution is (140-160) mg:6 mL:1 mL; and the concentration of the polyethyleneimine solution is 250.0 mg / mL.
4. The porous magnetic hydrogel according to claim 1, characterized in that: In step (3), the volume ratio of mixture A to mixture B is 4:(6-8).
5. Use of the porous magnetic hydrogel according to any one of claims 1 to 4 in the following (1) or (2): (1) Detection of nitrite; (2) Preparation of electrochemical sensor for detecting nitrite.
6. An electrochemical sensor for detecting nitrite in prepared dishes, characterized in that: The electrochemical sensor uses the glassy carbon electrode modified with the porous magnetic hydrogel according to any one of claims 1 to 4 as a working electrode.
7. The electrochemical sensor according to claim 6, characterized in that The electrochemical sensor also includes a reference electrode and an auxiliary electrode; the reference electrode is a saturated calomel electrode, and the auxiliary electrode is a platinum electrode.
8. A method for detecting nitrite in pre-prepared dishes, characterized in that: The following steps are involved: (1) The working electrode, reference electrode and auxiliary electrode in the electrochemical sensor according to claim 6 or 7 constitute a three-electrode system, and the working electrode is immersed in a nitrite standard solution of different concentrations and incubated within the window potential by differential pulse voltammetry, and the corresponding current value Ip is recorded; Ip is plotted with the concentration of the nitrite standard solution as the horizontal axis and the current value Ip as the vertical axis. P -C working curve; (2) Using the working curve drawn in step (1), the content of nitrite in the pre-treated prepared food sample to be tested is detected.
9. The detection method according to claim 8, characterized in that: In step (1), the window potential is 0.3-1.4 V; and the nitrite standard solutions of different concentrations are prepared from PBS solutions.
10. The detection method according to claim 8, characterized in that: In step (2), the pretreatment method of the pre-prepared dish to be tested is: adding a saturated borax solution and hot water to the pre-prepared dish sample to be tested, ultrasonically mixing and then boiling; cooling to room temperature, adding potassium ferrocyanide and zinc acetate solution to the extract, filtering after standing, evaporating the filtrate to dryness, and dissolving the residue with PBS.
